Methodological Approaches To Enhancing Lexical Awareness In Bilingual Students: Comparative Analysis Of Uzbek And Russian Lexicology (Eurasian Journal of Learning and Academic Teaching, 2026)
This study explores methodological approaches to enhancing lexical awareness in bilingual students through a comparative analysis of Uzbek and Russian lexicology. The research emphasizes the importance of developing learners’ vocabulary knowledge, phraseological competence, and semantic sensitivity in two linguistically and culturally distinct languages. By examining similarities and differences in lexical structures, word formation, and idiomatic expressions in Uzbek and Russian, the study highlights the role of contrastive analysis in language instruction. Pedagogical strategies such as semantic mapping, contextual exercises, and comparative textual analysis are discussed as effective tools for fostering bilingual students’ lexical and communicative competence.